Between Reading and Theatre: The Case of Les combustibles by Amélie Nothomb (Itinera, 2019)
Les combustibles (translated into Italian as Libri da ardere) is the third Amélie Nothomb work and her unique theatrical text.However, it can’t be considered as a canonical play, for its strong relationship with the page and the reader. The paper focuses on two theatrical versions produced by Teatro dell’Elfo in Milan in 2006 and 2018, adapted and directed by Cristina Crippa. The show maintains the link with the book through the declamation of stage directions by the three characters, in an experiment between reading and theatre. Combustibles, Nothomb, Cristina Crippa, Teatro dell’Elfo.